Service-Learning and Initial Teaching Training: a transformative relationship between Rural School and University for the promotion of digital technologies - Miró-Miró, Deli; Coiduras Rodríguez, Jordi; Molina-Luque, Fidel (Revista Complutense de Educación, 2021)
This article focuses on service-learning projects with primary school and university students doing initial teacher training in rural schools. The thread is the promotion of digital technologies that gives structure to an itinerary of audiovisual narratives as a means of reflection and intervention in the community environment with the participation of 32 rural schools in 12 Rural School Zones (ZER), in total, 798 primary school students and 50 students on the Bachelor’s Degree in Primary Education. The study aims to identify those categories of the greatest interest for the development of service-learning experiences in rural contexts on the basis of data provided by university students, through the application of a questionnaire and, all this vehiculated by the development of narratives that describe the progress of the projects. A quantitative methodological design is proposed. For the analysis of the quantitative data, SPSS statistical software is used. The results provide a questionnaire on the interest in initial teacher training of service-learning experiences in rural schools and a possible avenue of study on the educational possibilities of digital narratives in design and implementation processes of community actions for the exercise of citizenship committed to one's own reality.
Keywords: service-learning; initial teaching training; university; rural schools; questionnaire; digital narratives